Clinical and Histopathological Study of Sheep Pox in Ethiopia - Chanie, Mersha (International Journal of Natural Sciences, 2012)
Clinical signs, postmortem and histopathological lesions in sheep suffering from sheep pox were evaluated. Animals were selected purposively from Yemeze Gera Midir, Kalu and Kutaber district veterinary clinics, Ethiopia. Relevant data and samples were collected for the period from November, 2007 to December, 2009. Of the total 3263 sheep examined, 49.5% (1615) showed skin lesions, suppressed appetite and depression. The lesions were detected in all ages and both sexes. The chief clinical signs observed were: fever, macules, papules, nodules, enlarged lymph nodes, dyspnea, conjunctivitis, nasal discharge and labored and noisy breathing. The mortality rate was 10.42% (340). At postmortem, the skin showed necrotic lesions and scabs surrounded by areas of edema, hemorrhage and congestion. The mucous membranes of the eyes, nose, mouth, vulva and prepuce were ulcerated. The lungs contained edematous, congested, consolidated areas, and firm gray to white nodules. Papules and ulcerated areas were common on the abomasal mucosa. The histopathologic examination of hematoxylin and eosin and van Gieson stained skin biopsy sections taken from 21 sheep were done in Sebeta National Veterinary Diagnostic Center. The degree of damage on the skin varied from minimal to severe. The reaction to the virus range from few epidermal hyperplasia to different degrees of degeneration and necrosis of epidermis and dermis. DOI: http://dx.doi.org/10.3329/ijns.v1i4.9734 IJNS 2011 1(4): 89-92